Apelin attenuates oxidative stress in human adipocytes - Chen, Peng (2014)
It has been recently recognized that the increased oxidative stress (ROS overproduction) in obese condition is a key contributor to the pathogenesis of obesity-associated metabolic diseases. Apelin is an adipocytokine secreted by adipocytes, and known for its anti-obesity and anti-diabetic properties. In obesity, both oxidative stress and plasma level of apelin are increased. However, the regulatory roles of apelin on oxidative stress in adipocytes remain unknown. In the present study, we provide evidence that apelin, through its interaction with apelin receptor (APJ), suppresses production and release of reactive oxygen species (ROS) in adipocytes. This is further supported by the observations that apelin promotes the expression of anti-oxidant enzymes via MAPK kinase/ERK and AMPK pathways, and suppresses the expression of pro-oxidant enzyme via AMPK pathway. We further demonstrate that apelin is able to relieve oxidative stress -induced dysregulations of the expression of anti- and pro- oxidant enzymes, mitochondrial biogenesis and function, as well as release of pro- and anti- inflammatory adipocytokines. This study, for the first time, reveals the antioxidant properties of apelin in adipocytes, and suggests its potential as a novel therapeutic target for metabolic diseases.